Vitamin D status and clinical outcomes in incident dialysis patients: results from the NECOSAD study - Drechsler, Christiane; Verduijn, Marion; Pilz, Stefan; Dekker, Friedo W.; Krediet, Raymond T.; Ritz, Eberhard; Wanner, Christoph; Boeschoten, Elisabeth W.; Brandenburg, Vincent (Nephrology, dialysis, transplantation, 2011)
Background. The majority of dialysis patients suffer from vitamin D deficiency, which might contribute to an adverse health outcome. We aimed to elucidate whether European dialysis patients with low 25-hydroxyvitamin D (25(OH)D) levels are at increased risk of mortality and specific fatal events.Methods. This was a prospective cohort study of incident dialysis patients in the Netherlands (the NECOSAD). We selected all patients with measured 25(OH)D at 12 months after the start of dialysis, the baseline for our study. By Cox regression analyses, we assessed the impact of 25(OH)D levels on short-term (6 months of follow-up) as well as longer-term mortality (3 years of follow-up). Associations of 25(OH)D levels with cardiovascular and non-cardiovascular mortality were also determined.Results. The data from 762 patients (39% females, age 59 ± 15 years, 25(OH)D = 18 ± 11 ng/mL) were available. Fifty-one and 213 patients died during a follow-up of 6 months and 3 years, respectively. After adjustments for possible confounders, the hazard ratio (HR) (with 95% CI) for mortality was 2.0 (1.0-3.8) for short-term and 1.5 (1.0-2.1) for longer-term mortality when comparing patients with 25(OH)D levels ≤ 10 ng/mL with those presenting with 25(OH)D levels > 10 ng/mL. Adjusted HRs for cardiovascular mortality were 2.7 (1.1-6.5) and 1.7 (1.1-2.7) for short- and longer-term mortality, respectively. For non-cardiovascular mortality, we observed no relevant association overall. The impact of 25(OH)D levels on clinical events was modified by parathyroid hormone (PTH) status, with low 25(OH)D levels meaningfully affecting outcomes only in patients with PTH levels above the median of 123 pmol/L.Conclusions. Vitamin D deficiency in dialysis patients is associated with an adverse health outcome, in particular with short-term cardiovascular mortality. Intervention studies are urgently needed to evaluate whether vitamin D supplementation improves health outcomes of dialysis patients.